Prognostic effect of low-level HER2 expression in patients with clinically negative HER2 status - Hein, Alexander; Hartkopf, Andreas D.; Emons, Julius; Lux, Michael P.; Volz, Bernhard; Taran, Florin-Andrei; Overkamp, Friedrich; Hadji, Peyman; Tesch, Hans; Häberle, Lothar; Ettl, Johannes; Lüftner, Diana; et al. (European journal of cancer, 2021)
Purpose - Assessment of HER2 overexpression using immunohistochemistry (IHC) and/or in situ hybridisation (ISH) for the detection of HER2 amplifications is standard to identify patients for established HER2-directed treatments. Patients with lower HER2 expression levels have recently also become candidates for novel therapies targeting HER2. This study aimed to assess tumour and patient characteristics and prognosis in patients with advanced breast cancer (aBC), relative to low HER2 expression levels. - Methods - PRAEGNANT is a prospective aBC registry (NCT02338167), focusing on molecular biomarkers. Patients in all therapy lines receiving any kind of treatment are eligible. This analysis includes patients with conventionally HER2-negative aBC. Clinical outcome was compared in the groups with no (IHC score 0) or with low HER2 expression (IHC 1+, or IHC 2+/ISH negative). - Results - Low HER2 expression levels in triple-negative aBC patients did not influence progression-free survival. Overall survival appeared poorer in patients with IHC 2+ compared with patients with no HER2 expression in the unadjusted analysis (hazard ratio 2.24, 95% confidence interval 0.1.12-4.47). However, this effect was not maintained in the adjusted analysis. In HER2-negative, hormone receptor-positive patients, low HER2 expression appeared to have no effect on prognosis, neither progression-free survival nor overall survival. - Conclusions - We could not demonstrate that HER2 expression at a low level and assessed in clinical routine can differentiate patients into prognostic groups. However, the prevalence of patients with a low expression makes this population interesting for clinical trials with potentially active treatments using HER2 as a target.